(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
A study on Aluminium (Al) and Silicon (Si) in different Lake waters in different seasons around Dhaka city was carried out using Inductively Coupled Plasma-Atomic Emission Spectrophotometry (ICP-AES). The highest concentration of Si was found in March and lowest was in August in case of all the Lakes and Si concentration decreased in the order of Rupnagar Lake > Gulshan Lake > Ramna Lake > Dhanmondi Lake. On the other hand, in some cases, comparatively higher concentrations of Al were found in March and then these decrease in June and again increase in August indicating these lakes may be getting contamination during rainy season. Among the four Lakes, Al concentration decreased in the order of Dhanmondi > Ramna > Gulshan > Rupnagar. This may be due to the formation of hydroxyaluminosilicate at high total silicon concentration. It is also notable that the level of Al in these four Lakes is much higher than the Bangladesh drinking water standard for Al. Keywords : Lake water, seasonal variation, aluminium and silicon, ICP-AES doi: 10.3329/jbas.v32i1.2440 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 33-39, 2008